Intuitive Thinking Skills among Students of Faculties of Education at Tikrit University - Ghadban, Saad Habib (Journal of Tikrit University for Humanities, 2023)
The objective of this study was to assess the level of intuitive thinking abilities among students enrolled in the College of Education at the University of Tikrit. The study involved the research community comprising the departments of the College of Education for Human Sciences at the University of Tikrit. A sample of 114 students from the second stage was intentionally selected. The sample was divided into two experimental groups and a control group. The experimental group consisted of 57 students who received instruction on intuitive thinking skills. The research yielded a series of findings, with the most prominent being that there exists no statistically significant variation in intuitive thinking abilities among students enrolled in the College of Education.